Origin and Geochemical Processes of Porewater in Clay-Rich Deposits in the North Jiangsu Coastal Plain, China. (13th December 2017) - Ge, Qin; Liang, Xing; Jin, Menggui; Li, Jing; Liu, Yan
Abstract : The hydrogeochemical and stable isotope compositions of aquitard porewater samples from three boreholes were investigated to determine the origin, salinization, and hydrochemical evolution of water in the North Jiangsu coastal plain, China. Three porewater groups were identified based on the water-bearing subsystems. The total dissolved solids (TDS) of porewater samples highly varied from 0.03 to 26.1 g/L. Molar Cl/Br ratios and δ 18 O and δ 2 H data indicate that the source of Group 1 salinized porewater was the Holocene seawater, whereas Group 3 salinized samples were probably related to the remnant palaeoseawater of the Late Pleistocene. Group 2 samples had low salinity (TDS < 1 g/L) and undetectable Br − concentrations, which were probably recharged during a colder period and without evidence of seawater involvement. The salinized porewater was likely diluted by freshwater, as evidenced by its depleted isotopes and low salinity relative to standard seawater. The ionic ratios and ionic deltas indicate that considerable water-rock interactions (e.g., cation exchange and mineral weathering) also accounted for the hydrochemical constituents of porewaters, and cation exchange seems to be more noticeable at low salinity.